(3OQQ GdMcGe aj TQM ZQQ GdCMcGes - (3NSQh, eMeO Hf aQGeQR Hf Ydj, J (B885(3g`s ((3efUhQ Hf TYHGf GdbGOQjs)
(3ChdgG (B:s
(3cJGH GdMOhO(B. (3GdMO dZI(B: (3GdefY, hTQYG(B: (3YbhHI ebOQI NQL HgG GdJYRjQ EP dG JbOjQ ajg hdjS dg bOQ eYjf(B...s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gdg Ydjg hSde(B: (3ef GMJbQ UGMH GdYde agh edYhf aj GdOfjG hGdGNQI dCf dcd TjA YeGOG hYeGO GdTjWGf UGMH GdGeJMGf(B...s
(3JHUQI GdeDda (B:s
(3GdeYQha HedG, Ch efdG, Ch Gdehdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B328s
(3cTa GdXfhf(B: (3L(B2(3, U(B1199s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs